2020
DOI: 10.3991/ijet.v15i21.15647
|View full text |Cite
|
Sign up to set email alerts
|

Students Satisfaction with Online Learning Experiences during the COVID-19 Pandemic

Abstract: This research aims to evaluate the level of postsecondary student satisfaction with online learning platforms and learning experiences during the novel coronavirus COVID-19 pandemic in the Kingdom of Saudi Arabia (KSA). This paper is based on the premise of transformative learning theories [1], which describe the learners’ authority and investment over their learning. Quantitative research was carried out using a survey that was sent out to 283 students enrolled at one higher education institution in KSA. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
227
3
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(252 citation statements)
references
References 38 publications
12
227
3
10
Order By: Relevance
“…Numerous studies regarding online learning across higher education have been conducted, that have enhanced both the understanding and practical implications of adopting different modes of online learning, such as blended, asynchronous, and synchronous learning [15]. To determine the success of e-learning in higher education student satisfaction is an important indicator to determine performance [2,5,[8][9][10][11][12][13][14][15][16]. Duque (2013) proposed a framework for evaluating higher education performance with students' satisfaction, perceived learning outcomes, and dropout intentions, and found that dropout intentions were strongly and negatively associated with student satisfaction [32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous studies regarding online learning across higher education have been conducted, that have enhanced both the understanding and practical implications of adopting different modes of online learning, such as blended, asynchronous, and synchronous learning [15]. To determine the success of e-learning in higher education student satisfaction is an important indicator to determine performance [2,5,[8][9][10][11][12][13][14][15][16]. Duque (2013) proposed a framework for evaluating higher education performance with students' satisfaction, perceived learning outcomes, and dropout intentions, and found that dropout intentions were strongly and negatively associated with student satisfaction [32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This data shows that the pedagogical support to the student, which represents one of the most significant aspects of online education (UOC, 2020;Almusharraf & Khahro, 2020;Sánchez-Gelabert et al, 2020) is not satisfactory for large numbers of students.…”
Section: Student Supportmentioning
confidence: 92%
“…The former is extremely more important than the latter 2, 4,6,8 Middle values between two adjacent relationships Reciprocal Relationship between index j and index i, there is = 1/…”
Section: Value Of Qijmentioning
confidence: 99%
“…Nowadays, as the modern education technologies are becoming more and more intelligent, online learning is playing an increasingly important role in modern education [1][2][3][4]. However, since online learning is affected by a variety of constraints such as hardware facility, software system, teaching management, student self-learning, and course teaching implementation, etc., the manifestations of online learning effect and enhancement strategies have gradually become the focus of attention of field scholars [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%